Quality Assesment of Antibiotic Prescription for Sepsis Treatment in Intensive Care Unit at Top Referral Hospital in West Java, Indonesia - Shadrina Dinan Adani; Ardi Zulfariansyah; Putri Teesa Radhiyanti Santoso (Althea Medical Journal, 2017)
Background: Sepsis is a common disease in intensive care unit (ICU) with high mortality rate. Administration of antibiotic has an important role to determine the outcome of sepsis patient. This study aimed to evaluate the quality of antibiotic prescription for sepsis treatment in intensive care unit (ICU). Methods: This descriptive study was conducted by retrieving data from 48 medical records of patients with sepsis, severe sepsis, and septic shock admitted to ICU  Dr. Hasan Sadikin General Hospital (RSHS) in 2013. The study was conducted from August to October 2014. Empiric therapy in the ICUat RSHS and Surviving Sepsis Campaign (SSC) guidelines in 2012 were used as a standard for antibiotic prescription. The quality of antibiotic prescription was assessed then categorized based on Gyssens criteria. The collected data were analyzed in the form of frequency and percentage and presented in tables.Results: This study discovered that most of the patients had severe sepsis and septic shock. Based on Gyssens criteria, 35% antibiotic uses were included into category 0 (proper); 1.4% category I (improper timing); 10.5% category IIA (improper dosage); 9.1% category IIB (improper interval); 3.5% category IIC (improper route); 12.6% category IIIA (improper duration; too long); 1.4% category IIIB (improper duration; too short); 16.8% category IVA (improper; other antibiotics were more effective); 4.2% category IVD (improper; other antibiotics had narrower spectrum); and 5.6% category V (improper; no indication).Conclusions: There are still improper uses of antibiotic for sepsis, severe sepsis, and septic shock patients in the ICU. DOI: 10.15850/amj.v4n2.1088